Diversidade genética de uma Poaceae invasora aquática na região Neotropical. - Arjona, Bárbara Scorsim (2021)
Biological invasions are considered a very important topic of study, as they are considered one of the main causes of extinction and threats to local biodiversity. With regard to invasive aquatic plants in Brazil, representatives of Urochloa (Poaceae), coming from Africa have been highlighted in relation to their potential for invasiveness in Brazilian territory. However, the correct identification of the species included in this genus is doubtful, due to its morphological similarity with other species, which can influence the control measures. Thus, the objective was to carry out a molecular characterization and evaluate the genetic variability of the invasive exotic Poaceae Urochloa arrecta in five different Brazilian regions, especially those occurring in the upper Paraná River floodplain using the ITS nuclear marker and the chloroplast marker trnL-trnF. The sequences obtained were compared with those available from GenBank (NCBI). The results showed a low genetic variation for the sampled populations. Five and seven distinct haplotypes were identified for ITS and trnL-trnF, respectively. The data obtained may be useful for understanding the group's invasion mechanisms in the region.